BIMBINGAN KELOMPOK TEKNIK MODELLING SYMBOLIC UNTUK MENGURANGI KECENDERUNGAN OVER MAKE-UP PADA SISWI SMP - Enjelika Nor Rizki; Edris Zamroni; Indah Lestari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
The purpose of this study were: 1) To describe the implementation of group guidance services with symbolic modeling techniques to prevent the use of cosmetics in female students of SMPN 3 Bae Kudus, 2) To determine the effectiveness of the implementation of group guidance services using symbolic modeling techniques to prevent the use of cosmetics at school. This study used a quasi-experimental method with a one group pretest and posttest design. Before being given treatment in the form of group guidance services using the Symbolic Modeling technique, measurements were taken to determine the extent of students' understanding and discipline related to their appearance at school through a pretest, on 15 female students in class VIII D. The results showed that 9 students scored in the low category with an average value of 69, which means that they have not implemented a disciplined attitude to obey the rules and do not have an understanding of the proper use of cosmetics. Then after being given treatment in the form of group guidance services using the symbolic modeling technique, there was a significant increase of 51% to 120 with a high category on the posttest. This was also proven by the results of the analysis test using the Wilcoxon Test which obtained an Asymp value. Sig of 0.007 <0.05 which means Ha is accepted. So it can be concluded that the group guidance service of Symbolic Modeling technique is proven effective in preventing excessive use of cosmetics in class VIII D female students of SMPN 3 Bae Kudus.